Spatial and temporal variation and driving factors of wetland in the Amu Darya River Delta, Central Asia - Chanjuan Zan; Tie Liu; Yue Huang; Anming Bao; Yuyan Yan; Yunan Ling; Zheng Wang; Yongchao Duan (Ecological Indicators, 2022)
The Aral Sea in Central Asia has shrunk by 90% since 1960. The resulting desertification and salt and dust storms have diminished biodiversity in the Amu Darya River Delta, triggering the Aral Sea Crisis. Timely monitoring of trends and spatial patterns in deltaic wetlands is beneficial for biodiversity conservation and ecological restoration. Existing studies have mainly focused on the response of vegetation and microbial communities to ecological changes while ignoring the indicative role of wetlands-associated changes. This study analyzed the spatial and temporal patterns of long time series wetland changes extracted from remote sensing imagery through cover frequency maps and landscape indices. The hydrological data, land use/land cover change maps, and statistical data were combined to explore the driving factors of wetland change over the past 40 years. The results showed that the wetland area increased by 2242.96 km2 (90.72%) from 1977 to 2019. The wetland area increased at 268.01 km2/a from the 1970s to the early 1990s, with a fluctuating change since 1994. Wetlands are mainly distributed in the transition zone between the delta and the Aral Sea, accounting for approximately 81.61% of the total wetland area. The proportion of wetlands on the east and west sides significantly expanded along the canal system, increasing from 0.13% in 1977 to 9.74% in 2019. The degree of fragmentation of the wetland landscape in the entire delta increased by 1.7 times. With decreasing runoff into the delta, the expansion of cultivated land and the construction of reservoirs and irrigation canals changed the spatio-temporal distribution of water resources. In contrast, agricultural irrigation has raised the groundwater level. Human activities, such as the expansion of cultivated land and the construction of reservoirs and irrigation canals, are the main reasons for the spatio-temporal changes in wetland distribution, and exacerbated the decrease in water flow into the Aral Sea and its shrinkage. The restoration of wetlands is not a proof of ecological improvement, it resulted from the redistribution of water resources in the delta. The increase in wetland area represents an apparent ecological contrast with the drying up of the Aral Sea, and the phenomenon is not conducive to the ecological restoration of the delta.